NAVIGATORS: AN EDUCATIONAL GAME WITH VARIOUS INDIGENOUS TERRITORIES - dos Santos, Luiz Cláudio Machado; Winkler, Ingrid; Argolo, Daniel Fernandes; dos Santos, Bianca Bispo; Soares, Cainã Guimarães (Seven Editora, 2026)
Introduction: This article presents the development of a digital game that tells the story of four Indigenous peoples, addressing the curricular guidelines related to ethnic-racial issues, including Indigenous peoples. Objective: The objective is to introduce a mobile game in a 3D platform. Methodology or Steps: The methodological process involved a literature and systematic review focused on understanding the main Indigenous groups studied: the Māori, Inuit, Tuareg, and Yanomami peoples. After completing this stage, the construction of the Game Design Document began, aiming to create a game that would reflect the research findings. Results: As a result, a 3D mobile game was developed, showcasing the culture of four Indigenous peoples from different parts of the world.DOI: https://doi.org/10.56238/sevened2026.008-014